Theo em thì làm bằng Côsi ngược dấu như thế này:
[tex]2.VT = 1- \frac{a^2}{a^2 + 2} + 1 - \frac{b^2}{b^2+2} + 1 - \frac{c^2}{c^2+2}[/tex]
=[tex]3 - ( \frac{a^2}{a^2 + 2} + \frac{b^2}{b^2+2} + \frac{c^2}{c^2+2} )[/tex]
Mà [tex]\frac{a^2}{a^2 + 2} + \frac{b^2}{b^2+2} + \frac{c^2}{c^2+2} \geq \frac{(a+b+c)^2}{a^2+b^2+c^2+6}[/tex] - BDT Cauchy-Schwarz
Có [tex](a+b+c)^2[/tex] = [tex]a^2 + b^2 + c^2 + 2(ab+bc+ca)[/tex]
\Leftrightarrow [tex](a+b+c)^2 = a^2 + b^2 + c^2 +6[/tex]
\Rightarrow [tex]\frac{(a+b+c)^2}{a^2+b^2+c^2+6} =1 [/tex]
\Rightarrow 2.VT \leq 3 - 1 =2 \Rightarrow VT \leq 1 (đpcm).
Dấu = \Leftrightarrow a=b=c=1.